Investigating the Reliability and Dynamic Response of Fully 3D-Printed Thermistors - Umur Cicek; Darren Southee; Andrew Johnson (Applied Sciences)
This paper investigates the measurement capability, dynamic response, and mechanical reliability of all 3D-printed multi-material thermistors. The thermistor design consisted of three main components: a polycarbonate (PC) substrate, a silver (Ag) electrode pair, and a poly(3,4-ethylenedioxythophene):poly(4-styrenesulfonate) (PEDOT:PSS) thermosensitive layer. The thermistors were fabricated using two manufacturing techniques: fused deposition modeling (FDM) for the substrate and micro-dispensing for the Ag and PEDOT:PSS films. Two designs with different sensing areas, D1 (90 mm2) and D2 (54 mm2), were fabricated. As the indicator of measurement capability, the highest thermal indexes were recorded as 905.64 and 813.03 K for D1 and D2 thermistors, respectively. Thermistors exhibited comparable dynamic performance, with normalized resistance variations ranging from 0.96 to 1 for temperature changes between 25 and 45 °C. The sensing area influenced both measurement capability and dynamic performance, where larger sensing areas enhanced measurement capability but extended the time required to complete dynamic cycles, around 400 s for D1 versus 350 s for D2. Adhesion tests revealed a strong bonding between the PEDOT:PSS and Ag layer with less than 5% material removal. However, the adhesion of the PEDOT:PSS to the PC substrate was weak, with over 65% material removal. Morphological analysis indicated that the poor adhesion was caused by suboptimal surface properties of the 3D-printed substrate, even resulting in gaps between these two surfaces. This study demonstrates that our all 3D-printed multi-material thermistors can match reported measurement performance with an acceptable dynamic performance while highlighting the need to improve 3D-printed substrate surface properties to enhance the performance of such multi-material structures.